The ecologist's field guide to sequence‐based identification of biodiversity. Issue 9 (14th May 2016) - Creer, Simon; Deiner, Kristy; Frey, Serita; Porazinska, Dorota; Taberlet, Pierre; Thomas, W. Kelley; Potter, Caitlin; Bik, Holly M.
Summary: The past 100 years of ecological research has seen substantial progress in understanding the natural world and likely effects of change, whether natural or anthropogenic. Traditional ecological approaches underpin such advances, but would additionally benefit from recent developments in the sequence‐based quantification of biodiversity from the fields of molecular ecology and genomics. By building on a long and rich history of molecular taxonomy and taking advantage of the new generation of DNA sequencing technologies, we are gaining previously impossible insights into alpha and beta diversity from all domains of life, irrespective of body size. While a number of complementary reviews are available in specialist journals, our aim here is to succinctly describe the different technologies available within the omics toolbox and showcase the opportunities available to contemporary ecologists to advance our understanding of biodiversity and its potential roles in ecosystems. Starting in the field, we walk the reader through sampling and preservation of genomic material, including typical taxonomy marker genes used for species identification. Moving on to the laboratory, we cover nucleic acid extraction approaches and highlight the principal features of using marker gene assessment, metagenomics, metatranscriptomics, single‐cell genomics and targeted genome sequencing as complementary approaches to assess the taxonomic and functional characteristics of biodiversity. We additionally provide clear guidance on the forms of DNA found in the environmental samples (e.g. environmental vs. ancient DNA) and highlight a selection of case studies, including the investigation of trophic relationships/food webs. Given the maturity of sequence‐based identification of prokaryotes and microbial eukaryotes, more exposure is given to macrobial communities. We additionally illustrate current approaches to genomic data analysis and highlight the exciting prospects of the publicly available data underpinning published sequence‐based studies. Given that ecology 'has to count', we identify the impact that molecular genetic analyses have had on stakeholders and end‐users and predict future developments for the fields of biomonitoring. Furthermore, we conclude by highlighting future opportunities in the field of systems ecology afforded by effective engagement between the fields of traditional and molecular ecology.